The Effectiveness of the Existence of Village Customary Courts in Utilizing Problem Solving By the Bireuen Community - Andi Lesmana Lesmana; Munawir Munawir (JED (Jurnal Etika Demokrasi), 2022)
The authority of the Village customary court in Aceh qanun No. 9 of 2008 concerning fostering customs. One of them is giving the authority to resolve civil and criminal disputes which are part of the authority of formal justice, with this delegation giving the role of the Adat Courts is very important. Bireuen for this research is used for the specific objectives of this study aims to measure the extent to which the village customary justice in the district. Bireuen is used by the community. The method used is an empirical juridical method with a quantitative research methodology that used a research instrument in the form of a questionnaire. The existence of customary courts which have reached 15 years since their publication of a qanun gave legitimacy to gampong customary courts in Aceh, especially Bireuen district.